The influence of 17beta-estradiol on annexin 1 expression in the anterior pituitary of the female rat and in a folliculo-stellate cell line. - Davies, E; Omer, S; Morris, J; Christian, H (2007)
Annexin 1 (ANXA1) is a Ca2+- and phospholipid-binding protein that plays an important role as a mediator of glucocorticoid action in the host-defence and neuroendocrine systems. Sex differences in hypothalamo-pituitary-adrenal (HPA) axis activity are well documented and a number of studies have demonstrated that gonadal steroids act as regulators of HPA activity. The aim of this study was to investigate the effect of ovariectomy and 17beta-estradiol replacement, and estrous cycle stage, on anterior pituitary ANXA1 content. The amount of anterior pituitary ANXA1 determined by western blotting varied with estrous cycle stage with a peak at estrus declining to a trough at proestrus. Ovariectomy resulted in a significant (P<0 x 05) decrease in anterior pituitary ANXA1 content. Administration of 17beta-estradiol (1 microg/100 g) significantly (P<0 x 01) increased anterior pituitary ANXA1 expression in the ovariectomized animals. In contrast, there was no change in pituitary ANXA1 content in response to 17beta-estradiol in adrenalectomized and adrenalectomized/ovariectomized rats. Treatment of TtT/GF cells, a folliculo-stellate cell line, with 17beta-estradiol (1 x 8-180 nM) increased ANXA1 mRNA expression and increased the amount of ANXA1 protein externalized in response to a dexamethasone stimulus. These results indicate that 17beta-estradiol stimulates ANXA1 expression in the anterior pituitary and in vivo an adrenal factor contributes to the mechanism of action.